PERLAWANAN TOKOH UTAMA PEREMPUAN TERHADAP PATRIARKI DALAM NOVEL PEREMPUAN YANG MENANGIS KEPADA BULAN HITAM KARYA DIAN PURNOMO - Eza Risti Arifa (fakultas sastra, 2022)
This study aims to describe the form of patriarchal practice in novel Perempuan yang Menangis kepada Bulan Hitamby Dian Purnomo. The theory used in this research is Sylvia Walby's patriarchal theory. The research method used is a descriptive method with a qualitative approach. The data used are in the form of dialogue excerpts and sentences in novel Perempuan yang Menangis kepada Bulan Hitam by Dian Purnomo which describes the form of patriarchal practice and the form of resistance of the main female character in the novel, using the data source of novel Perempuan yang Menangis kepada Bulan Hitam by Dian Purnomo. The data collection technique used is the citation note technique and the data analysis technique used is the content analysis technique. From the findings of the form of patriarchal practice and the form of resistance of the main female character in novel Perempuan yang Menangiskepada Bulan Hitam by Dian Purnomo, the data analyzed were 37 data. The results of this study indicate that the form of patriarchal practice consists of 24 data which is divided into three forms, namely the form of patriarchal practice consists of 6 data, patriarchal practice in the form of violence consists of 11 data, and patriarchal practice in the form of sexuality consists of 7 data. The form of deep patriarchal practice is dominated by male violence against women in the form of beating husbands against wives and attempted rape. Then, the resistance of the main female character against patriarchy found as many as 13 research data.Kata Kunci/Keywords: patriarchal practices, violence, sexuality, novel, Sylvia Walby